Inclination of the condylar long axis is not related to temporomandibular disc displacement - Amorim, Marian Y. [UNESP]; Alves, Monica G. O. [UNESP]; Almeida, Janete D. [UNESP]; Montesinos, Gonzalo A. P.; Costa, Andre L. F.; Lopes, Sergio L. P. de C. [UNESP] (Wiley-Blackwell, 2019)
Aim The aim of the present study was to correlate the angle formed by inclination of the condylar long axis and median sagittal plane to the presence of internal disc derangement, as well as changes in eccentric mandibular positions. Methods The sample consisted of magnetic resonance images of 35 temporomandibular joint (TMJ) acquired with a 1.5T magnetic resonance imaging system with surface coils of 8.5 cm in diameter. Parasagittal images were used according to the following parameters: TMJ disc position with mouth closed, TMJ disc position with mouth open, TMJ disc function, and degrees of rotation and translation of the condyle. Next, we determined the angles between the condyle long axis and median sagittal plane by using axial images. Results The results showed correlations between TMJ disc position and disc function (P = 0.009), as well as between disc position and degree of condylar rotation (P = 0.008). The main purpose of the present study was to assess the angle of the condylar long axis, with no statistical correlation being found between this variable and disc position (P = 0.787), disc function (P = 0.091), condylar translation (P = 0.808), and condylar rotation (P = 0.115). Conclusion There was no relationship between inclination of the condyle long axis and parameters of internal derangements.
Keywords: articular disc; condylar long axis; magnetic resonance imaging; median sagittal plane; temporomandibular joint